2015
DOI: 10.1111/jeb.12770
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genetic consequences of facultative sex and outcrossing

Abstract: This is an invited review by the winner of the 2015 John Maynard Smith prize, awarded annually by the European Society for Evolutionary Biology to an outstanding young evolutionary biologist. Keywords:adaptation; asexuality; genomics; selfing; sexual reproduction. AbstractExplaining the selective forces that underlie different reproductive modes forms a major part of evolution research. Many organisms are facultative sexuals, with the ability to reproduce both sexually and asexually. Reduced sequencing costs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 202 publications
5
109
1
Order By: Relevance
“…As illustrated in Figure S1, this regime may be particularly important in highly selfing populations and when the deleterious mutation rate U is high, since N e may be sufficiently reduced to affect the efficiency of selection at an important proportion of selected sites. This is confirmed by empirical observations of higher ratios of nonsynonymous to synonymous polymorphism (p N =p S ) in selfing lineages than in their outcrossing relatives (Glémin and Muyle 2014;Hartfield 2015 and references therein), indicating that a significant fraction of deleterious alleles may increase in frequency due to drift (in which case the assumption that N e s 1 at most loci is not valid). It is thus important to keep in mind that background selection models such as the one presented here overestimate the reduction in N e in such situations, and it would be interesting (although probably challenging) to obtain analytical predictions for neutral diversity in populations undergoing low rates of sex or high selfing rates and in which selection against a high proportion of deleterious mutations is rendered ineffective.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…As illustrated in Figure S1, this regime may be particularly important in highly selfing populations and when the deleterious mutation rate U is high, since N e may be sufficiently reduced to affect the efficiency of selection at an important proportion of selected sites. This is confirmed by empirical observations of higher ratios of nonsynonymous to synonymous polymorphism (p N =p S ) in selfing lineages than in their outcrossing relatives (Glémin and Muyle 2014;Hartfield 2015 and references therein), indicating that a significant fraction of deleterious alleles may increase in frequency due to drift (in which case the assumption that N e s 1 at most loci is not valid). It is thus important to keep in mind that background selection models such as the one presented here overestimate the reduction in N e in such situations, and it would be interesting (although probably challenging) to obtain analytical predictions for neutral diversity in populations undergoing low rates of sex or high selfing rates and in which selection against a high proportion of deleterious mutations is rendered ineffective.…”
Section: Discussionmentioning
confidence: 50%
“…Analyses based on molecular data show little evidence for increased ratios of nonsynonymous to synonymous substitutions (d N =d S ) in selfing lineages that would indicate a reduced efficiency of purifying selection (Glémin and Muyle 2014;Hartfield 2015 and references therein): this may be due to the recent origin of those lineages or to the low rates of outcrossing maintained by most predominantly selfing species ). However, several recent studies showed elevated ratios of nonsynonymous to synonymous polymorphism (p N =p S ) in various selfing species (compared with their outcrossing relatives), suggesting that deleterious alleles may reach higher frequencies in selfers (e.g., Brandvain et al 2013;Burgarella et al 2015; and other references listed in table 1 of Hartfield 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That male behaviour can have a strong effect on the likelihood of observing sexual reproduction becomes arguably more plausible in the case of facultative sex, where the same organism can perform either sexual or asexual life cycles [12]. Which one is employed at any given time can depend on environmental conditions, competition and also-interestingly for our topic-on the availability of males.…”
Section: Introductionmentioning
confidence: 97%
“…These consequences include the increased probability of going extinct due to the accumulation of harmful mutations (Lynch et al 1995a,b) and an increased rate of speciation which may be driven by higher among-population differentiation and reproductive assurance that facilitates colonization of new habitats (Baker 1955;Hartfield 2016). The advantages of reproductive assurance may explain why transitions to SC occur repeatedly (Igic et al 2008;Lande and Schemske 1985).…”
Section: Model Comparisons and Error Ratesmentioning
confidence: 99%